Sixth Graders’ Selection and Integration When Writing from Multiple Online Texts - Gonzalez-Ibanez, R (Springer Science and Business Media B.V., 2023)
This study examined students’ ability to select relevant ideas from multiple online texts and integrate those ideas in their written products. Students (N = 162) used a web-based platform to complete an online inquiry task in which they read three texts presenting different perspectives on computer gaming and wrote an article for a school magazine on the issue based on these texts. Students selected two snippets from each text during reading and wrote their article with the selected snippets available. The selected snippets were scored according to their relevance for completing the task, and the written products were scored according to their integration quality. The results showed that most students performed well on the selection task. However, nearly half of the written products were characterized by poor integration quality. The hierarchical multiple regression analysis showed that students’ selection of relevant ideas from the texts contributed to their integration of information across texts over and above both reading fluency and reading comprehension skills. The study provides new evidence on the relationship between selection and integration when younger students work with multiple texts, and both theoretical and educational implications of these findings are discussed. © 2022, The Author(s).